Escenarios de cambio climático, capacidad germinativa de cuatro especies forestales en una gradiente altitudinal simulando un incremento de temperatura en el Corredor de Conectividad Podocarpus – Yacuambi - Luzuriaga Carpio, Ronny Xavier (2014)
Climate changes projections may affect the distribution of plant species whose survival depends on the ability to adapt to those changes. This study was conducted in order to determine the quality of Tabebuia chrysantha, Nectandra membranacea, Morella pubescens and Heliocarpus americanus seeds and evaluate the percentage of germination in different temperature conditions and humidity in the Podocarpus – Yacuambi Connectivity Corridor at south- eastern of Ecuador. For this quality parameters of seeds were collected and measured to further establish experimental parcels in three altitudinal gradients, monitoring both germination as temperature and humidity conditions. The results obtained show that the seeds of those four species have good quality but low germination and thanks to its low moisture content can be stored for long periods of time. On the other hand the germination test results show that all species respond differently to different temperature and humidity conditions, showing different degrees of resilience of species to different climate scenarios.